Analytical Hierarchy Process in The Assessment of The Best Teacher In the Category of Learning Activity Management System - Dodi Guswandi; Hadi Syahputra; Agung Ramadhanu; Yogi Wiyandra; Suci Wahyuni (Jurnal KomtekInfo, 2021)
The implementation of online lectures using blended learning needs to be assessed to find out the performance activities of lecturers with students in using the learning activity management system (LAMS) feature and reward lecturers with the best performance. Based on the assessment system of the best lecturers previously have not used the right methods so that the resulting decision is still not right and not accurate. This research aims to implement the Analytical Hierarchy Process (AHP) method in the assessment process of lecturers who are the best in using LAMS. The performance of the AHP method can determine the weight value of criteria consistently and can perform a role to produce solutions in decision making. The criteria indicators used to consist of Interactive Video Teaching Materials (C1), Audio Teaching Materials (C2), URLs (C3), Forum/FBL (C4), Slide Teaching Materials (C5), Assignments (C6), Quiz (C7), Attendance (C8), and Labels (C9). The results of this study showed that the performance of the Decision Support System (DSS) using the AHP method can determine a better weight value with a consistency level of 0.080049762 from 0.1. These results presented with AHP performance can provide weighting value on each criterion and continue the multiplication process with the best lecturer assessment data to get the results of the battle. Overall these results concluded that each criterion had a degree of consistent relationship in the best lecturer assessment on LAMS.